2015
DOI: 10.1186/s12937-016-0159-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nutritional intake on disease severity in children with sickle cell disease

Abstract: BackgroundChildren with Sickle Cell Disease (SCD) may show growth failure in comparison to healthy peers. Many factors as hematological status, endocrine and/or metabolic dysfunction, and nutritional status, may play an important role in growth failure. The aim of this study was to assess whether impaired growth and nutritional intake can affect SCD severity during childhood.MethodsWe conducted an observational study on children with SCD referring to our clinic for routine follow-up visits in a 6-month period.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 27 publications
2
21
0
1
Order By: Relevance
“…Albumin (g/L) 39.0 6 3.4 38.6 6 4.1 39 6 4.5 0.9 Serum ferritin (ng/ml) 167.0 6 173.8 117.9 6 181.3 154.0 6 164.6 0.5 WBC (10 3 /mL) 10.4 6 5.2 10.8 6 4.9 9.8 6 5.5 0.4 RBC (10 6 /m L) 3.4 6 1.2 3.3 6 0.9 3.5 6 1.4 0.3 Hb (g/dL) 8.6 6 1.7 8.4 6 1.8 8.7 6 1.7 0.6 HCT (%) 27.2 6 5.9 26.9 6 5.8 27.4 6 5.9 0.7 MCV (fL) 80.6 6 11.3 81.5 6 12.4 79.2 6 9.6 0.3 MCH (pg) 25.8 6 3.3 25.9 6 3. Children with SCD have higher metabolic rate and resting energy expenditure, and this may increase metabolic and nutrient demands; thus inadequate nutrient intake makes children with SCD susceptible to undernutrition, which increases disease severity (Mandese et al, 2015). Anthropometric measures reflect the nutritional and growth status of children with SCD.…”
Section: Resultsmentioning
confidence: 99%
“…Albumin (g/L) 39.0 6 3.4 38.6 6 4.1 39 6 4.5 0.9 Serum ferritin (ng/ml) 167.0 6 173.8 117.9 6 181.3 154.0 6 164.6 0.5 WBC (10 3 /mL) 10.4 6 5.2 10.8 6 4.9 9.8 6 5.5 0.4 RBC (10 6 /m L) 3.4 6 1.2 3.3 6 0.9 3.5 6 1.4 0.3 Hb (g/dL) 8.6 6 1.7 8.4 6 1.8 8.7 6 1.7 0.6 HCT (%) 27.2 6 5.9 26.9 6 5.8 27.4 6 5.9 0.7 MCV (fL) 80.6 6 11.3 81.5 6 12.4 79.2 6 9.6 0.3 MCH (pg) 25.8 6 3.3 25.9 6 3. Children with SCD have higher metabolic rate and resting energy expenditure, and this may increase metabolic and nutrient demands; thus inadequate nutrient intake makes children with SCD susceptible to undernutrition, which increases disease severity (Mandese et al, 2015). Anthropometric measures reflect the nutritional and growth status of children with SCD.…”
Section: Resultsmentioning
confidence: 99%
“…Results revealed depleted selenium and vitamin E levels in children with TM and SCD relative to healthy controls, which supports the findings of the current study where participants had significantly lower corrected plasma vitamin E levels than reference levels. Mandese et al, also found children with SCD to have many vitamin deficiencies, including vitamin E [16].…”
Section: Discussionmentioning
confidence: 96%
“…With great interest, I have read an article by Mandese et al [ 1 ], recently published in Nutrition Journal. The study reported on the nutritional status among children with sickle cell disease (SCD) in relation to disease severity and other morbidity outcomes.…”
Section: To the Editormentioning
confidence: 99%
“…The study reported on the nutritional status among children with sickle cell disease (SCD) in relation to disease severity and other morbidity outcomes. The authors reported a negative correlation between fetal hemoglobin levels and the intake of carbohydrates, lipids, iron, phosphorus, vitamins B1, and B2, suggesting a beneficial effect that low intake of these nutritional elements [ 1 ]. However, I would like to highlight two points.…”
Section: To the Editormentioning
confidence: 99%
See 1 more Smart Citation